Indicator of change management: learning organization and strengthening process - Nurul Sahadila Abd Rani; Mohd Izham Mohd Hamzah (Penerbit Universiti Kebangsaan Malaysia, 2020)
The mission of the Ministry of Education Malaysia is to create a world-class quality education system and to develop individual potential. This study aimed to identify the level of change indicators in the District Education Office (PPDs) and also to explore the implementation of the change indicators in strengthening PPDs. The study was conducted using the Explanatory Sequential Design approach, involving 93 Heads of PPDs who were selected using group sampling techniques and strata random sampling. Data was analyzed through SPSS. Then, a qualitative study was conducted, involving 13 Officers at PPDs who were purposively chosen through snowball sampling. Data was gathered through semistructured interviews and themes were developed and analyzed with NVivo 11. The results show that the level of change indicators in the PPDs are at high; hence, qualitative findings show six themes of change indicators in PPDs, signifying that the indicators of change management in PPDs had been implemented well. The implications of this study provide added value and are used as a reference for PPDs to monitor and provide an early intervention if any issue was detected in the implementation of the change programme. Indepth studies are recommended to explore the factors that influence the success of change and practice of PPDs learning organization.